Brahms: a multi-agent modelling environment for simulating work processes and practices. (1st October 2007) - Sierhuis, Maarten; Clancey, William J.; Van Hoof, Ron J.J.
Modelling and simulating work processes is often done at such an abstract level that individual work practice ? collaboration, communication, 'off-task' behaviours, multi-tasking, interrupted and resumed activities, informal interactions, use of tools and movements ? is left out, making the description of how the work in an organisation actually gets done impossible. This paper describes the Brahms modelling and simulation environment, developed at NASA Ames Research Center. The Brahms modelling language is geared towards modelling people's activity behaviour, making it an ideal environment for simulating organisational processes at a level that allows the analysis of the work practice and designing new work processes at the implementation level.